Working outside the employer's premises: Legal regime and organizational challenges during and after the pandemic of the infectious disease Covid-19 - Ristić Andrijana (Glasnik Advokatske komore Vojvodine, 2023)
The outbreak of the epidemic of the infectious disease Covid-19 has resulted in greater relevance for working outside an employer's premises all around the world. As, until then, this way of organizing work was not so frequent, due to the cautious attitude of employers and employees towards it, the regulation of this issue was not given adequate attention at the domestic and international levels. In this paper, the author will try to answer the question of whether the attitudes of employees and employers towards this manner of organizing work have changed after the emergence of extraordinary epidemiological circumstances and whether, as a result, it will become more frequent in the future. In addition, the author will try to determine whether work outside the employer's premises is adequately regulated in the Republic of Serbia, as well as whether and which issues need to be more comprehensively regulated in light of its increased importance. To obtain answers to the abovementioned questions, the author conducted a survey with employees who, due to the introduction of the state of emergency in the Republic of Serbia, began to work outside the employer's premises. The stated results will be evaluated in light of the results of surveys conducted at the level of the European Union, while the regulations regarding this way of organizing work will be considered via an analysis of laws and by-laws that regulate this issue in the Republic of Serbia.